FRUITY-SCAPE : fruits in landscape - Mohd Tahir, Osman (University Putra Malaysia, 2012)
Landscape is the environment experienced by individuals which includes the flora and fauna, and the patterns of human activities. It is an interaction between natural resources and human needs comprising an appreciation of beauty and aesthetic values, ecology and history of the area. This chapter discusses three aspects of the fruit trees in different landscape areas which relate to the fruity-scape of the area.